2020
DOI: 10.15587/1729-4061.2020.213236
|View full text |Cite
|
Sign up to set email alerts
|

Determining the quality of milk fat dispersion in a jet-slot milk homogenizer

Abstract: the production of most dairy products [1, 2]. The purpose of homogenization is a dispersion (reduction) of the average diameter of fat globules (ADFG) of milk from 3-4 μm in nonprocessed milk to 0.75-0.85 μm in a finished product. Such values correspond to dispersion characteristics of valve 1. Introduction Milk homogenization improves the taste of dairy products and extends their shelf life, so it belongs to standard operations used in the dairy industry. It is conducted in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 20 publications
(59 reference statements)
0
0
0
Order By: Relevance
“…The results of analytical studies of JSHM confirmed by experimental studies indicate the possibility of obtaining a product whose ADMFD is 0.75-0.85 μm [11,46]. At the same time, the energy costs of dispersion are 0.70-0.80 kWh/t [47,48].…”
Section: Type Of Homogenizermentioning
confidence: 90%
See 4 more Smart Citations
“…The results of analytical studies of JSHM confirmed by experimental studies indicate the possibility of obtaining a product whose ADMFD is 0.75-0.85 μm [11,46]. At the same time, the energy costs of dispersion are 0.70-0.80 kWh/t [47,48].…”
Section: Type Of Homogenizermentioning
confidence: 90%
“…At the same time, the course of the process below the liquid level allows avoiding the phenomenon of foaming. Nevertheless, according to the results of analytical studies, the SEC of such a device is 1.3-1.5 kWh/t [11,40]. Relatively high values of electricity consumption of this design are explained by additional energy consumption.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations